2020
DOI: 10.3390/genes11101161
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Genetic and Gene Technologies in Shaping Modern Rapeseed Cultivars (Brassica napus L.)

Abstract: Since their domestication, Brassica oilseed species have undergone progressive transformation allied with the development of breeding and molecular technologies. The canola (Brassica napus) crop has rapidly expanded globally in the last 30 years with intensive innovations in canola varieties, providing for a wider range of markets apart from the food industry. The breeding efforts of B. napus, the main source of canola oil and canola meal, have been mainly focused on improving seed yield, oil quality, and meal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 161 publications
0
14
0
Order By: Relevance
“…Brassica napus (AACC, 2 n = 38), formed by hybridization between the diploid ancestors of B. rapa (AA, 2 n = 20) and B. oleracea (CC, 2 n = 18), is widely cultivated worldwide as both an oilseed and a vegetable ( Fujii and Ohmido, 2011 ; Ton et al, 2020 ). The purple leaf trait and the mechanisms underlying the anthocyanin accumulation has been widely documented in B. rapa and B. oleracea ( Zhang et al, 2014 and, 2015 ; He et al, 2016 ; Xie et al, 2016 ; Song et al, 2018 ; Guo et al, 2019 ; Yan et al, 2019 ); however, few studies have investigated Brassica napus anthocyanin biosynthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Brassica napus (AACC, 2 n = 38), formed by hybridization between the diploid ancestors of B. rapa (AA, 2 n = 20) and B. oleracea (CC, 2 n = 18), is widely cultivated worldwide as both an oilseed and a vegetable ( Fujii and Ohmido, 2011 ; Ton et al, 2020 ). The purple leaf trait and the mechanisms underlying the anthocyanin accumulation has been widely documented in B. rapa and B. oleracea ( Zhang et al, 2014 and, 2015 ; He et al, 2016 ; Xie et al, 2016 ; Song et al, 2018 ; Guo et al, 2019 ; Yan et al, 2019 ); however, few studies have investigated Brassica napus anthocyanin biosynthesis.…”
Section: Introductionmentioning
confidence: 99%
“…The use of phylogenetic tools has permitted many genera and species to be grouped according to conventional taxonomic techniques. A phylogenetic tree was created using the Mega X program and the findings suggested that the origin was diverse [ 20 , 45 , 46 ]. Sequences from a gene bank of different species were a dominant method of classification [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Rapeseed oil obtained from B. napus seed is different from linoleic acid and linolenic acid, as oleic acid is relatively stable and has the valuable characteristic of reducing blood cholestrol. 48 Epidemiological studies have shown that residents in Mediterranean countries live longer and have lower rates of cardiovascular disease and breast cancer, which are closely related to the widespread consumption of olive oil rich in oleic acid. 49 Therefore, reducing the content of polyunsaturated fatty acid in edible rapeseed oil and increasing the content of oleic acid are some of the important goals of rapeseed quality breeding.…”
Section: ■ Discussionmentioning
confidence: 99%